2019
DOI: 10.1055/s-0039-1677904
|View full text |Cite
|
Sign up to set email alerts
|

Serious Games in Health Professions Education: Review of Trends and Learning Efficacy

Abstract: Objectives: To provide an overview of research trends and a review regarding the learning efficacy of serious games for health professions education taking into account short-term learning outcomes. Methods: For the review of research trends, we performed the search on Web of Science from 1996 until the present. For the scoping review on learning efficacy, ERIC, Education Source, PsychINFO, Global Health, CINAHL, Web Of Science, and Medline were searched. Results: The publications trend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 43 publications
1
52
0
6
Order By: Relevance
“…An important strength of our study is that it responds to the call for more insight into aspects that contribute to achieving goals in both delirium education and serious games [ 1 , 3 , 4 , 25 – 27 , 71 , 72 ]. Our findings can be used to inform future development of delirium education and serious games.…”
Section: Discussionmentioning
confidence: 99%
“…An important strength of our study is that it responds to the call for more insight into aspects that contribute to achieving goals in both delirium education and serious games [ 1 , 3 , 4 , 25 – 27 , 71 , 72 ]. Our findings can be used to inform future development of delirium education and serious games.…”
Section: Discussionmentioning
confidence: 99%
“…The number of results when searching in Google Academics using the words escape, room, classroom, higher, and education gives an indication of the level of interest of these activities (initially designed as leisure activities) in university contexts. Moreover, in a study developed for analyzing serious games in health education, authors found a growth in the number of publications about this topic [2]. This increase is also reflected in an online survey from The Codex (https://thecodex.ca/), a group of escape game enthusiasts, who observed that the number of people interested in this topic had doubled in 2018 [3].…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies on serious games in medical education have been reported in recent years [ 16 - 18 ], these studies often investigated serious games as whole artifacts without focusing on the effect of different play strategies such as dark play. In a previous study, we showed that dark play did not affect game effectiveness [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the allocation to a specific play strategy in the previous study, little is yet known about how often students voluntarily choose dark play in a serious game, which students choose to engage in dark play and why, and what they gain from their experience. By gaining insight on these aspects, we may meet the demand of more research on game elements that promote engagement and support the learning of players [ 16 , 18 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%